The Influence of Parental Attachment on the Independence of 5-6 Years Old Children - Syifa Liwahul Rochmah; Kristiana Maryani; Fahmi Fahmi (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2023)
This research is motivated by the problem of low child independence. The purpose of this study was to determine the effect of attachment on the independence of children aged 5-6 years. Using a quantitative research approach with the ex-post facto method. The population used in this study were 176 children aged 5-6 years in RA throughout the District of Jombang - Cilegon, Banten. Sampling using the slovin formula as many as 63 children. Data collection techniques using questionnaires, with data analysis techniques to test the hypothesis t. Based on the findings regarding attachment to the independence of children aged 5-6 years that there are children who have high independence, the attachment of parents is high and vice versa. Children's independence is seen in children's behavior while in the school environment and outside of school. The results of attachment research on the independence of children aged 5-6 years show a significant value of 0.034 <0.05, so it can be interpreted that there is a significant influence between attachments on the independence of children aged 5-6 years.